Slow burn summer : a novel - Silver, Josie (Delacorte Press, 2025)
"She's playing the part of romance author, but has she found her own real-life love story? Talent agent Charlie Francisco has three problems: a divorce that ended his screenwriting career, a business he never planned to inherit, and a take-your-breath-away romance novel whose author wants nothing to do with its publication. The book is a surefire hit, if only his agency can find someone to "play" author on its summer book tour. Enter Kate Elliott, a former soap actress who's miraculously right for the part at the very moment her life seems to be going all wrong. Kate is still recovering from her own divorce and Charlie's job offer is a lifeline. She agrees to the pretense for all interviews, signings, and appearances surrounding the novel's publication. But she can't know who really wrote the remarkable story--the one so beautiful it's made her believe in love again. When Kate and Charlie meet they're all friction and sparks--the one thing they have in common is they're determined to play their respective parts. But as the summer heat ups and the lies get bigger and bigger, can they stick to their lines . . . or will they go off-script?"--